EKSPERIMEN PENGGUNAAN BAHASA JEPANG MATA PELAJARAN KAIWA MENGGUNAKAN MODUL DI SMA 2 MALANG - Muhammad Muhammad; Djodjok Soepardjo; Didik Nurhadi (ITB AAS Indonesia Surakarta, 2023)
This article presents a study on the efficacy of learning tools (Kaiwa Card and Modul) for reading Kaiwa among students in SMA 2 MALANG during the academic year 2017/2018. Japanese writing involves the use of Katakana, Hiragana, and Kaiwa, which can be challenging for learners. Therefore, learners require learning material specific to Kaiwa. Kaiwa Card and Modul are two such learning materials that are user-friendly, suitable for all educational levels, cost-effective, and engaging for learners. The study employed a pretest-posttest control group design, with a sample size of 62 students, 32 in class A (using Moduls) and 30 in class B (using Kaiwa Card). Multiple-choice tests and questionnaires were used as research instruments. Based on the data analyzed, the t-count was found to be less than t-table (0.426 vs. 2.000) at a 5% significance level, thus confirming Ho and rejecting Hk. Therefore, Moduls were found to be more effective than Kaiwa Card for reading Kaiwa. However, both Kaiwa Card and Modul were found to be suitable and interesting for Kaiwa learning, as reported in the questionnaire.